Mengungkap Naskah Kuna Koleksi Masyarakat Cirebon: Sebuah Catatan Filologis sebagai Trend Studi Islam di PTAI - Mahrus el-Mawa (Masyarakat Pernaskahan Nusantara, 2011)
Philological studies under the Ministry of Religious Affairs of the Republic of Indonesia, through State Islamic Higher Education Institutions (PTAI), are currently becoming a trend. This can be seen from several initiatives undertaken, both practically and strategically. Among the PTAIs referred to in this paper is IAIN Syekh Nurjati Cirebon. The manuscripts discussed in this paper are related to the heritage of the Cirebon Palace/Sultanate, especially Kasepuhan and Kanoman, currently held by the community. These two palaces represent two of the four Palaces in Cirebon. Both play an important role in Islamic civilization in Indonesia. Among these roles is the presence of ancient religious manuscripts, parts of which have been saved by their heirs as community collections to this day. This paper reveals the access to and identity of the Palace's ancient manuscripts held within the community, particularly following a digitization effort conducted together with public Islamic higher education institutions in Cirebon. It is hoped that there will be a more strategic follow-up for the preservation and conservation of ancient manuscripts as evidence of Indonesian Islamic civilization by various parties. The following discussion is also equipped with a simple description of several of these manuscripts. === Studi filologi di Kementrian Agama RI, melalui Perguruan Tinggi Agama Islam (PTAI), saat ini tengah menjadi trend. Hal itu bisa dilihat dari beberapa ikhtiar yang telah dilakukannya, baik secara praktis maupun strategis. Diantara PTAI yang dimaksud dalam tulisan ini adalah IAIN Syekh Nurjati Cirebon. Naskah yang diungkap dalam paparan ini terkait dengan warisan Kraton/Kesultanan Cirebon, terutama Kasepuhan dan Kanoman yang berada di masyarakat. Kedua kraton ini merupakan dua dari empat Kraton di Cirebon. Keduanya mempunyai peran penting dalam peradaban Islam di Indonesia. Diantara perannya antara lain adanya naskah kuna (manuscript) keagamaan yang hingga kini, sebagiannya diselamatkan para pewarisnya sebagai koleksi masyarakat. Tulisan ini mengungkap akses dan identitas naskah kuna Kraton yang di masyarakat, khususnya setelah digitalisasi bersama-sama PTAIN di Cirebon. Harapannya, terdapat tindak lanjut yang lebih strategis untuk penyelamatan dan pelestarian naskah kuna sebagai bukti dari peradaban Islam Indonesia oleh berbagai pihak. Paparan berikut ini dilengkapi pula dengan deskripsi sederhana dari beberapa naskah tersebut.